A dimmable LED light source along the Planckian locus - Yuanbao Du; Lixia Zhao; Riguang Zhang; Yaohua Zhang (iScience)
Summary: Multiple channels are designed for dimmable LED light sources with color temperatures ranging from 2,700 to 6,500 K. However, issues such as Delta uv (Duv) values <0, lower brightness, luminous efficacy, and color rendering index (CRI), lower power density, exceeding the standard deviation of color matching (SDCM), unconstant power, poor color consistencies, and high costs persist. We present a three-channel LED light source featuring an integrated chip-on-board (COB) package structure. The channels are separated by a white dam to reduce reabsorption problems and improve color consistencies between different color temperatures. Additionally, the complementary channel M uses layered phosphor excitation for more accurate and efficient spectral compensation during dimming. Ultimately, this solution enables dimming along the Planck curve with constant power, improving CRI, luminous efficacy, and brightness at intermediate temperatures, while being cost-effective and minimizing the impact on initial color temperatures, offering a high-quality dimmable LED option for intelligent applications.